Analyzing International Students' Social Support Through Intercollegiate Sport Team Identification - Kim, Kibaek; Stokowski, Sarah; Lo, Wen Juo; Han, Jinwook (Journal of International Students, 2022)
International students often experience difficulties acclimating to campus climates in the United States. While identifying oneself as a fan of college sports has been shown to assist domestic students in their social adjustment to college environments, little is known about the relationship between international students’ college sports team identification and their social adjustment. As such, the purpose of this study is to determine the effect of team identification on international students’ sense of community and social capital and the conceptual relationship between the sense of community and social capital. Analysis of the hypothesized model with a sample of international students (n = 487) revealed that international students’ team identification develops their sense of community and social capital. Implications focused on how the international student office and athletic departments can utilize intercollegiate sport to support international students and assist this population in adapting to campus life in the United States.